2007
DOI: 10.1073/pnas.0611639104
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor coactivator 3 is a coactivator for myocardin, the regulator of smooth muscle transcription and differentiation

Abstract: Abnormal proliferation of vascular smooth muscle cells (VSMCs) constitutes a key event in atherosclerosis, neointimal hyperplasia, and the response to vascular injury. Estrogen receptor ␣ (ER␣) mediates the protective effects of estrogen in injured blood vessels and regulates ligand-dependent gene expression in vascular cells. However, the molecular mechanisms mediating ER␣-dependent VSMC gene expression and VSMC proliferation after vascular injury are not well defined. Here, we report that the ER coactivator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…To the best of our knowledge differences in apparent versus deduced MW of MYOCD proteins have not been recognized in previous studies on mouse myocd (Creemers et al, 2006b;Xing et al, 2006;Wang et al, 2004Wang et al, , 2007. On the other hand, one can deduce from published SDS-gel images (see Qiu et al, 2005;Li et al, 2007) that an apparent MW of FLAG-tagged mouse MYOCD seems to be between 120-130 kDa that is similar to the MW value of myc/His-tagged porcine MYOCD-A (this work). It seems that the presence of myc/His residues (see Fig.…”
Section: Which Porcine Myocardin Gene To Use For Delivery?mentioning
confidence: 56%
“…To the best of our knowledge differences in apparent versus deduced MW of MYOCD proteins have not been recognized in previous studies on mouse myocd (Creemers et al, 2006b;Xing et al, 2006;Wang et al, 2004Wang et al, , 2007. On the other hand, one can deduce from published SDS-gel images (see Qiu et al, 2005;Li et al, 2007) that an apparent MW of FLAG-tagged mouse MYOCD seems to be between 120-130 kDa that is similar to the MW value of myc/His-tagged porcine MYOCD-A (this work). It seems that the presence of myc/His residues (see Fig.…”
Section: Which Porcine Myocardin Gene To Use For Delivery?mentioning
confidence: 56%
“…Hence, the significantly higher amounts of ERα and ERβ in the USL of patients affected by POP may contribute to mechanisms repairing stretch injury, as has been described in pelvic ligament fibroblasts as well as in blood vessels after artificial trauma [19]. In those vessels the proliferation of vascular smooth muscle cells was mediated via ERα [20]. Thus, the altered ERα expression may reflect a reaction to tissue stretch injury and part of the ligamental repair process rather than a cause for lower ligamental Fig.…”
Section: Discussionmentioning
confidence: 87%
“…There are still no data about how estrogen was linked to the SRF-CArG box interaction, but a recent study by Li et al [41] found that SRC3, an ER coactivator could bind to myocardin and enhance its transcriptional activity in vascular SMCs.…”
Section: Discussionmentioning
confidence: 96%